1989
DOI: 10.2514/3.45826
|View full text |Cite
|
Sign up to set email alerts
|

Computational simulation of vortex generator effects on transonic shock/boundary-layer interaction

Abstract: T HE present work describes a theoretical simulation of the effects of a vortex generator row ahead of a shock/boundary-layer interaction zone. The row is represented by parameters characterizing the Law of the Wall/Law of the Wake structure of the turbulent boundary layer. This model is then integrated into a previously developed twodimensional computational code that utilizes an appropriate triple-deck theory of a nonseparating shock/bbundary-layer interaction. The results imply that the shape factor reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Downstream of the SBVGs the main shock resembles that seen in the uncontrolled interaction, except that the foot is distinctly smaller. This contraction of the foot appears to confirm the conclusions of Inger and Siebersma [17] that VGs reduce the size of the interaction region. The boundary layer thickens significantly at the main shock position for both devices.…”
Section: Subboundary Layer Vortex Generatorssupporting
confidence: 88%
See 1 more Smart Citation
“…Downstream of the SBVGs the main shock resembles that seen in the uncontrolled interaction, except that the foot is distinctly smaller. This contraction of the foot appears to confirm the conclusions of Inger and Siebersma [17] that VGs reduce the size of the interaction region. The boundary layer thickens significantly at the main shock position for both devices.…”
Section: Subboundary Layer Vortex Generatorssupporting
confidence: 88%
“…This observation is of interest because it ties in with shock-control methods such as passive devices [2,[9][10][11], active control [2] using blowing [2] or suction [12,13], and 2-D [14,15] or 3-D bumps [16], which work by generating compression waves that smear the shock-induced pressure rise. However, Inger and Siebersma [17] showed numerically that VGs upstream of a shock energize the boundary layer, thereby reducing the shape factor and increasing the pressure gradient and shock strength across the interaction. This paper presents an investigation into the effect of SBVGs upstream of a separated shock/boundary layer interaction (SBLI) and aims to determine whether such devices can have a shock weakening effect.…”
mentioning
confidence: 98%
“…These vortices can be shed by inserting traditional or sub-boundary layer vortex generators into the flow [129]. Through their research in transonic flow, Inger and Siebersma (1989) showed that placing vortex generators upstream of the contact point energizes the incoming boundary layer wave [130]. As a result, the pressure gradient around the contact zone rises, ultimately creating a strong shock.…”
Section: Passive Control Techniquesmentioning
confidence: 99%
“…(Passive control) [105,121,[129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] Very efficient in suppressing the separated shear layer by energizing the incoming boundary layer through vortices.…”
Section: Mvgsmentioning
confidence: 99%